If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (X + -1)(x + -9) = 0 Reorder the terms: (-1 + X)(x + -9) = 0 Reorder the terms: (-1 + X)(-9 + x) = 0 Multiply (-1 + X) * (-9 + x) (-1(-9 + x) + X(-9 + x)) = 0 ((-9 * -1 + x * -1) + X(-9 + x)) = 0 ((9 + -1x) + X(-9 + x)) = 0 (9 + -1x + (-9 * X + x * X)) = 0 (9 + -1x + (-9X + xX)) = 0 Reorder the terms: (9 + -9X + -1x + xX) = 0 (9 + -9X + -1x + xX) = 0 Solving 9 + -9X + -1x + xX = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9X + -1x + -9 + xX = 0 + -9 Reorder the terms: 9 + -9 + -9X + -1x + xX = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -9X + -1x + xX = 0 + -9 -9X + -1x + xX = 0 + -9 Combine like terms: 0 + -9 = -9 -9X + -1x + xX = -9 Add 'x' to each side of the equation. -9X + -1x + x + xX = -9 + x Combine like terms: -1x + x = 0 -9X + 0 + xX = -9 + x -9X + xX = -9 + x Reorder the terms: 9 + -9X + -1x + xX = -9 + x + 9 + -1x Reorder the terms: 9 + -9X + -1x + xX = -9 + 9 + x + -1x Combine like terms: -9 + 9 = 0 9 + -9X + -1x + xX = 0 + x + -1x 9 + -9X + -1x + xX = x + -1x Combine like terms: x + -1x = 0 9 + -9X + -1x + xX = 0 The solution to this equation could not be determined.
| 21+10x=12x-16 | | 5/12=x/4 | | Y-6=8y | | 14+3x+2x+15=54 | | 3v+12v=-15 | | 3x+6-2x-8=30 | | =0.55555555556 | | 144=-129(x+5) | | 486+.03x=490+.02x | | 8(10+7v)= | | H(t)=-16t^2+150t+162 | | h(9)=8 | | n-9+13=16 | | 3x+4y+5w= | | 7x*21y=28 | | 1.24x+7.7=82.1 | | 1-9+13=16 | | sin(2x)=10cosx | | (-2/7)÷(3/5) | | 10=u+v | | -33=a+9+6a | | 3(12x-16)=4(12-3x) | | 5x+125=10x | | 20=a/b | | 8k-9k=-3 | | 2x+3x+6+2=-12 | | 9q=63 | | 3=3/4(8-w) | | 3=-5(3)-2 | | u=v+20forv | | 2/3-0.25 | | 4x+1=74 |